105 Inappropriate ICD Shocks in a Patient with Dilated Cardiomyopathy and Broca's Aphasia. (14th February 2019) - Georgi, Christian; Neuß, Michael; Möller, Viviane; Seifert, Martin; Butter, Christian
Abstract : With a growing number of ICD recipients, device complications are seen more frequently in the clinical setting and outpatient departments. Among the most severe are ICD infections and inappropriate therapies caused by oversensing of atrial tachycardias or lead fracture. We report on a 76-year-old female patient with dilative cardiomyopathy and Broca's aphasia after stroke, who experienced 105 consecutive inappropriate ICD shocks due to cluster missensing of her fractured ICD lead. The diagnosis was complicated and delayed by patient's aphasia emphasizing the need for intensified remote monitoring along with regular in-person visits, especially in people with intellectual or communication disabilities.